Understanding abortion-related complications in health facilities: results from WHO multicountry survey on abortion (MCS-A) across 11 sub-Saharan African countries - Özge Tunçalp; Cassimo Bique; Ahmet Metin Gülmezoglu; Veronique Filippi; Richard Adanu; Bela Ganatra; Bukola Fawole; Philip Govule; Zahida Qureshi; Luis Gadama; Seni Kouanda; Caron Rahn Kim; et al. (BMJ Global Health)
Introduction Complications due to unsafe abortions are an important cause of morbidity and mortality in many sub-Saharan African countries. We aimed to characterise abortion-related complication severity, describe their management, and to report women’s experience of abortion care in Africa.Methods A cross-sectional study was implemented in 210 health facilities across 11 sub-Saharan African countries. Data were collected on women’s characteristics, clinical information and women’s experience of abortion care (using the audio computer-assisted self-interviewing (ACASI) system). Severity of abortion complications were organised in five hierarchical mutually exclusive categories based on indicators present at assessment. Descriptive bivariate analysis was performed for women’s characteristics, management of complications and reported experiences of abortion care by severity. Generalised linear estimation models were used to assess the association between women’s characteristics and severity of complications.Results There were 13 657 women who had an abortion-related complication: 323 (2.4%) women were classified with severe maternal outcomes, 957 (7.0%) had potentially life-threatening complications, 7953 (58.2%) had moderate complications and 4424 (32.4%) women had mild complications. Women who were single, multiparous, presenting ≥13 weeks of gestational age and where expulsion of products of conception occurred prior to arrival to facility were more likely to experience severe complications. For management, the commonly used mechanical methods of uterine evacuation were manual vacuum aspiration (76.9%), followed by dilation and curettage (D&C) (20.1%). Most frequently used uterotonics were oxytocin (50∙9%) and misoprostol (22.7%). Via ACASI, 602 (19.5%) women reported having an induced abortion. Of those, misoprostol was the most commonly reported method (54.3%).Conclusion There is a critical need to increase access to and quality of evidence-based safe abortion, postabortion care and to improve understanding around women’s experiences of abortion care.